2010
DOI: 10.3748/wjg.v16.i46.5838
|View full text |Cite
|
Sign up to set email alerts
|

Translation and validation of the Greek chronic liver disease questionnaire

Abstract: Our data confirmed the validity of the Greek version of the CLDQ in identifying the QOL among patients with chronic liver disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
15
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 16 publications
2
15
0
1
Order By: Relevance
“…The overall CLDQ score as well as the domain sub scores showed an inverse relationship with the disease severity. Similar pattern of association between Child Pugh Score and CLDQ has been demonstrated by other studies also 3,11,16,[23][24][25] . The post-hoc analysis revealed that the average and the sub scores of patients with Child C were significantly low than patients with both Child A and B, however most of the studies using CLDQ have not been able to differentiate between Child C and B 3,6,26 .…”
supporting
confidence: 66%
See 2 more Smart Citations
“…The overall CLDQ score as well as the domain sub scores showed an inverse relationship with the disease severity. Similar pattern of association between Child Pugh Score and CLDQ has been demonstrated by other studies also 3,11,16,[23][24][25] . The post-hoc analysis revealed that the average and the sub scores of patients with Child C were significantly low than patients with both Child A and B, however most of the studies using CLDQ have not been able to differentiate between Child C and B 3,6,26 .…”
supporting
confidence: 66%
“…Similar kind of new factor named as 'sleep' has been previously described by the Italian, 9 Spanish, 8 German, 11 and Chinese 15 studies also where the authors have discussed the cultural differences in the sleeping habits. Likewise, a Serbian 22 study found a higher degree of belonging of item number 27 (Itching) to the domain of 'sleep' rather than 'systemic symptoms'.…”
mentioning
confidence: 76%
See 1 more Smart Citation
“…O domínio físico avalia facetas como dor e desconforto, energia e fadiga, sono e repouso, mobilidade, atividade de vida cotidiana, dependência de medicação ou de tratamentos e capacidade de trabalho: assim sendo, esta associação seria esperável e já foi encontrada em estudos que avaliaram a qualidade de vida em hepatopatas 14,30 . No campo das relações sociais, os resultados encontrados também não diferiram de estudos anteriores, que encontraram escores mais elevados entre os mais jovens 8,31 . Os achados relativos à ocupação -pacientes que não trabalhavam tiveram níveis mais baixos de qualidade de vida nos domínios físico e social que aqueles que estudavam e/ou estavam empregados -podem refletir um aspecto específico do domínio físico que é a avaliação da capacidade para o trabalho e são consistentes com o resultado do estudo de Ohaeri et al 32 .…”
Section: Qualidade De Vida E Variáveis Sociodemográficasunclassified
“…The Chronic Liver Disease Questionnaire (CLDQ) is the most widely validated disease‐specific HRQOL instrument developed for patients with CLD . The CLDQ has been cross‐culturally validated and translated into several different languages worldwide and has demonstrated excellent validity and reliability for the assessment of HRQOL in CLD irrespective of language, cultural differences, educational level, and etiology of liver disease . Despite this, measurement of HRQOL is not commonly performed in clinical practice.…”
Section: Introductionmentioning
confidence: 99%